Nurses' Practices With Persons Experiencing Opioid Use Disorder: A Narrative Literature Review. Issue 1 (January 2022) - Sowicz, Timothy Joseph; Huneycutt, Brittany; Lee, Jung Min
Abstract: Millions of persons globally use opioids, and more than two million persons in the United States report having opioid use disorder (OUD). Increases in overdose deaths associated with opioids have led to a declaration of an opioid epidemic in the United States. Many healthcare professionals are involved in the treatment of persons experiencing OUD; several discipline-specific (e.g., medicine and public health) interventions are available. Nurses comprise large portions of the global and national healthcare workforces; therefore, investigating their unique, disciplinary contributions for addressing the opioid epidemic is warranted. This narrative literature review was undertaken to understand nurses' actions, practices, and work with persons with OUD. Using several databases and keywords, 21 research studies met the inclusion criteria. Most studies used qualitative designs; most quantitative studies were nonexperimental. The studies were conducted mostly in Europe and North America. Descriptions of nurses' practices with people with OUD varied in their levels of specificity and aligned well with the scopes of practice outlined by the American Nurses Association and the International Nurses Society on Addictions. The absence of theories (specifically nursing theories) used in the studies was notable. Theoretically informed studies that move beyond descriptions of nurses' practices are needed to advance discipline-specific knowledge and to showcase the unique contributions of nurses who make significant contributions to lessening adverse outcomes associated with OUD.